2021
DOI: 10.1152/japplphysiol.00990.2020
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar muscle atrophy and increased relative intramuscular lipid concentration are not mitigated by daily artificial gravity after 60-day head-down tilt bed rest

Abstract: Exposure to axial unloading induces adaptations in paraspinal muscles, as shown after spaceflights. This study investigated whether daily exposure to artificial gravity (AG) mitigated lumbar spine flattening and muscle atrophy associated with 60-day head-down tilt (HDT) bed rest (Earth-based space analogue). Twenty-four healthy individuals participated in the study: Eight received 30 minutes continuous AG; eight received 6x5 minutes AG, interspersed with rest periods; eight received no AG exposure (control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 71 publications
(86 reference statements)
2
14
0
Order By: Relevance
“…The study size of 24 was selected based on previous HDTBR studies showing the protective effects of AG on bone resorption [29] and orthostatic tolerance [30]. Other measures from this study have been published elsewhere and showed that HDTBR induced increases in spinal length and area of lumbar intervertebral discs, a reduction in the lumbar lordosis, and atrophy of the LM, LES, and QL muscles [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study size of 24 was selected based on previous HDTBR studies showing the protective effects of AG on bone resorption [29] and orthostatic tolerance [30]. Other measures from this study have been published elsewhere and showed that HDTBR induced increases in spinal length and area of lumbar intervertebral discs, a reduction in the lumbar lordosis, and atrophy of the LM, LES, and QL muscles [28].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, artificial gravity (AG), via centrifugation in a short-arm centrifuge, has been suggested to mitigate many of these effects by stimulating the proprioceptive, vestibular, and neuroendocrine systems [26,27]. As AG is associated with a large acceleration gradient along the body axes (»1G z at the lumbar vertebral level), it has also been proposed that a mechanical compressive force applied to the lumbar spine could stimulate the lumbar muscles [28]. It is unknown whether the increased ILC in the lumbar musculature in response to exposure to prolonged HDTBR is homogeneous within the muscles and spinal levels or with spatial variation of accumulation, or whether this can be mitigated by exposure to AG.…”
Section: Introductionmentioning
confidence: 99%
“…MRIs were assigned a random code to ensure blinding of the measurer to time points and participant groups. Other imaging data from this study pertaining to the lumbar spine region, including muscle volume and ILC, have been published elsewhere ( De Martino et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…Head-down tilt (HDT) bed rest studies provide an accelerated model of lumbar spine deconditioning ( Hargens and Vico, 2016 ), which can be used to test novel rehabilitation procedures after periods of reduced axial loading with minimal confounding factors. Studies using magnetic resonance imaging (MRI) have demonstrated atrophy of the lumbar multifidus (LM), lumbar erector spinae (LES), and quadratus lumborum (QL) muscles and hypertrophy of the psoas major (PM) muscle after HDT bed rest ( Hides et al, 2007 ; Belavý et al, 2010 ; De Martino et al, 2021b ). Specific exercises focused on the recruitment and training of lumbopelvic muscles have been shown to reverse some of these adaptations ( Hides et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specific exercises focused on the recruitment and training of lumbopelvic muscles have been shown to reverse some of these adaptations ( Hides et al, 2011 ). Magnetic resonance imaging can be used to quantify both muscle size and properties of muscle tissue, such as paraspinal muscle fat content (PFC) ( Elliott et al, 2013 ), which has been shown to increase in the LM and LES muscles after 60-days of HDT bed rest ( De Martino et al, 2021b ) and spaceflight ( Burkhart et al, 2019 ; McNamara et al, 2019 ). To date, no studies have investigated whether reconditioning programs after HDT bed rest can fully reverse the increased PFC in the lumbopelvic muscles.…”
Section: Introductionmentioning
confidence: 99%